Assessing the Cascading Effect of Energy and Transport Critical Infrastructure Elements: Case Study - Brabcova, Veronika; Slivkova, Simona; Rehak, David; Toseroni, Fulvio; Havko, Jan (Communications - Scientific letters of the University of Zilina, 2018)
This article focuses on the issue of assessing the cascading effects of critical energy and transport infrastructure elements at the fundamental level. The introductory part deals with the typology of failures and their impacts, which spread through the critical infrastructure system. At this stage, the paper presents current approaches to assessing the cascading effects and, in particular, addresses a newly developed assessment methodology. The following part defines the initial conditions of assessment and describes selected elements from the areas of energy and rail transport to which the methodology will be subsequently applied. The main part of the article is a case study of the proposed methodology, assessing the cascading effects by calculating the value of their risks, depending on the resilience and correlation of the rated elements.